Governance of Administrative Services In Wunut Village Porong District Sidoarjo District - Choiriyah, Ilmi; Hanun, Nur; Widhitama, Krisna (Jurnal Administrasi Pemerintahan Desa, 2021)
This research discusses village governance, which is an important aspect of government administration at the village level. With a focus on Wunut Village, Porong District, Sidoarjo Regency, this research aims to initiate and improve the governance of village administrative services in order to improve the quality of public services at the local level. The research method used is qualitative with a descriptive approach, referring to the basic principles of effective administrative governance. Data collection was carried out through interviews, observation and documentation, with the selection of informants using the purposive sampling method. The research results show that although the village government has made efforts to organize village government management, there are still several obstacles that hinder its efficiency and effectiveness. These obstacles include a lack of transparency in providing information to the community, a lack of compliance with applicable regulations, and a lack of fairness in the distribution of tasks between village officials. Based on research analysis and conclusions, it is recommended that district and sub-district governments carry out regular outreach, training and assistance regarding village governance. Village officials also need to increase their professionalism and pay attention to the equipment needed to manage village government. Apart from that, it is necessary to implement a good village information system supported by electronic media to facilitate access to information for the community and increase the efficiency of data storage and management. In conclusion, improving the quality of village government is an important step in improving public services and community welfare at the local level.